2015
DOI: 10.1103/physrevd.91.063010
|View full text |Cite
|
Sign up to set email alerts
|

Dark fluid or cosmological constant: Why there are different de Sitter-type spacetimes

Abstract: Many different forms of the de Sitter metric in different coordinate systems are used in the general relativity literature. Two of them are the most common, the static form and the cosmological (exponentially expanding) form. The staticity and non-stationarity of these two different forms are traced back to the noncomoving and comoving nature of the corresponding coordinate systems. In this paper using the quasi-Maxwell form of the Einstein field equations and a definition of static spacetimes based upon them,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…13 As cold dark matter appears to do, in agreement with observations [39]. 14 The debate on the ability to distinguish ΛCDM from a dark fluid is still open [42].…”
Section: The Cosmographic Energy Conditionssupporting
confidence: 71%
“…13 As cold dark matter appears to do, in agreement with observations [39]. 14 The debate on the ability to distinguish ΛCDM from a dark fluid is still open [42].…”
Section: The Cosmographic Energy Conditionssupporting
confidence: 71%
“…But they were found to be genuinely different from de Sitter space, when their curvature invariants as well as their dynamical forms in the comoving synchronous coordinate systems were calculated. These findings motivated the idea that one should consider a perfect fluid nature for the cosmological term and assign a 4-velocity to the fluid particles, in order to be able to interpret the preferred directional expansion of the de Sitter-type spacetimes in their dynamical forms [3].…”
Section: Introductionmentioning
confidence: 79%
“…Indeed this case has been thoroughly discussed in [3], where it is shown that it leads to a unique characterization of de Sitter and de Sitter-type spacetimes as the only one-component static perfect fluid solutions of Einstein field equations in a non-comoving frame. The well known de sitter spacetime…”
Section: Static and Stationary Perfect Fluid Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawking modes from the de sitter cosmological horizon W begin the examples of this section with the de Sitter cosmological horizon, while for a discussion of the comparative physics of the de Sitter spacetime in static and dynamic patches we refer to [32]. The static patch of the de Sitter spacetime is defined by the metric, ds r dt r dr r d 1 3 1 3…”
Section: 1mentioning
confidence: 99%